Reproductive Indices and Oxidative Stress Biomarkers of Male Wistar Rats Prenatally Exposed to Cigarette Smoke (Nigerian Journal of Physiological Sciences, 2019)
Summary: The negative influence of cigarette smoking on developing fetus is well documented but reports of prenatal cigarette smoking on male reproductive hormones are controversial. However, shortened anogenital distance (AGD) has been established to be an indicator of potential male infertility. We therefore investigated the effects of prenatal exposure to passive cigarette smoke on AGD, reproductive hormones and oxidative stress biomarkers of Wistar rats. Female rats were randomly divided into two groups (n=5) and cohabited with male. Group 1 was exposed to smoke from an idling cigarette from day 1 of gestation till parturition, while Group 2 served as control (no-exposure). Morphometric variables of the litters were recorded on postnatal day 1 (PND1) and at 6th week postnatal life. The male offspring were then sacrificed by cervical dislocation. Testosterone, luteinizing hormone (LH) and follicle stimulating hormone (FSH) were analysed using ELISA. Serum levels of Catalase, sodium dismutase (SOD), malondialdehyde (MDA), lipid profile and liver function biomarkers were examined spectrophotometrically. On PND1, crown rump length and total body length of rats prenatally exposed to cigarette smoke were significantly shorter. Significantly shorter AGD and crown rump length were also observed at 6th week. Testosterone, LH and FSH were not significantly affected. Cigarette smoke exposure significantly decreased Catalase and SOD while MDA increased. Liver function biomarkers, HDL and LDL were not affected but serum levels of total cholesterol and triglyceride significantly increased. The observed decline in AGD and precipitation of oxidative stress by intrauterine cigarette smoke exposure may predispose to male infertility at adulthood.